DAMPAK KENAIKAN HARGA BAHAN BAKAR MINYAK (BBM) TAHUN 2022 TERHADAP TINGKAT PENDAPATAN PEDAGANG DI PASAR CAKRANEGARA KOTA MATARAM - Reza Setiawan; Rosita (Yayasan Nusantara Hasana Berdikari, 2023)
The increase in fuel prices always has an impact on rising production costs and transportation costs. The increase in production costs will affect the increase in the price of goods or inflation in the country. The increase in fuel prices will always be followed by an increase in commodity prices which can then increase the inflation rate. In addition, traders will automatically have to adjust the price of their merchandise from the increase in fuel prices. This study used a qualitative method with a total of 494 traders and the respondents who were taken were traders with various types of businesses such as convection, sandals, fruits, side dishes, electronics, and auto parts traders. The results showed that the income of the convection business was higher than the income after the increase in fuel prices, the type of sandal business had decreased or stabilized, the type of sandal business remained because it provided selling products through online media (buy online), the type of fruit business Fruits are stable because they take goods from their own area (local), the type of side dishes business which is a primary human need so fuel prices go up, consumers continue to buy products from side dishes, the type of electronic business has not decreased and the increase (stable) has been adjusting product prices with the cost of transportation costs, the type of spare parts business has decreased because they have not adjusted the prices of the products they sell with the prices of transporting goods from outside the island.